2015
DOI: 10.1016/j.jlumin.2015.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Transparent organic light-emitting diodes with different bi-directional emission colors using color-conversion capping layers

Abstract: We report a study on transparent organic light-emitting diodes (OLEDs) with different bidirectional emission colors, enabled by color-conversion organic capping layers. Starting from a transparent blue OLED with an uncapped Ag top electrode exhibiting an average transmittance of 33.9%, a 4-(Dicyanomethylene)-2-methyl-6-(4-dimethylaminostyryl)-4H-pyran (DCM)-doped tris-(8-hydroxy-quinolinato)-aluminium (Alq3) capping layer is applied to achieve color-conversion from blue to orange-red on the top side while main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The chemical structures of the materials and energy level diagrams used in this study are shown in Figs. 2 and 3 (the energy levels are taken from the literature) [8]- [10], respectively. ITO was cleaned using a standard oxygen plasma treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical structures of the materials and energy level diagrams used in this study are shown in Figs. 2 and 3 (the energy levels are taken from the literature) [8]- [10], respectively. ITO was cleaned using a standard oxygen plasma treatment.…”
Section: Methodsmentioning
confidence: 99%